Simulation of photovoltaic-thermal collectors coupled with domestic hot water system in Singapore's HDB buildings - Teo, Hwee Chuan (Nanyang Technological University, 2022)
In response to climate change, the adoption of renewable energy like solar photovoltaic (PV) has consistently received growing worldwide acceptance in recent years. In Singapore, where land is limited, most of the PV systems have to be installed on building rooftops. However, solar radiation that reaches the PV panels is only partially converted into electricity, the majority of the solar irradiation will be trapped as residual heat in the panels. This will increase the temperature of the PV panels and cause reduction in the solar to electricity conversion efficiency and a host of other problems such as Urban Heat Island effect in cities and affect inhabitants near to the PV installations. Photovoltaic-thermal (PVT) technology is an improvement with additional solar collector attachment to the PV panel to harvest the residual solar thermal energy. PVT has received attention mainly in cold countries to utilise the solar thermal as a useful heat reserve. PVT systems have been integrated into residential buildings for water heating and indoor space warming. Their use is well-documented in cold countries but not in Singapore where heat is already abundant. Therefore, this project served to evaluate the potential of PVT in Singapore. The PVT-DHW system design was proposed in this project to provide hot water supply in HDB buildings for daily household activities like showering. Simulation approach was used to study the feasibility of PVT collectors coupled with an independent domestic hot water (DHW) supply system on the rooftops of Housing Development Board (HDB) residential buildings. TRNSYS was the choice of simulation tool due to its flexibility and reputation amongst energy professionals around the world. The findings of the simulation confirmed that the PVT-DHW system design to harvest the renewable solar thermal energy and store in DHW could have both technical and economic potentials to replace the existing practice of using local electric water heaters to provide hot water supply for daily household activities in HDB households.